One voice is all you need: a one-shot approach to recognize you - Dipto, Shahriar Rumi; Nowshin, Priata; Ahmed, Intesur; Chowdhury, Deboraj; Noor, Galib Abdun (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.